M&S Smart System contrast sensitivity measurements compared to standard visual function measurements in primary open angle glaucoma patients - Liu, Jessica (J Glaucoma, 2017)
PURPOSE: To evaluate the nature and extent of letter contrast sensitivity (CS) deficits in glaucoma patients using a commercially available computer-based system (MSSS-II) and to compare the letter CS measurements to standard clinical measures of visual function. METHODS: Ninety-four subjects with primary open-angle glaucoma participated. Each subject underwent visual acuity, letter CS, and standard automated perimetry (SAP) testing (Humphrey SITA 24-2). All subjects had a best-corrected visual acuity (BCVA) of 0.3 log MAR (20/40 Snellen equivalent) or better and reliable SAP (fixation losses, false positives, and false negatives < 33%). Contrast sensitivity functions (CSFs) were estimated from the letter CS and BCVA measurements. The area under the CSF (AUCSF), which is a combined index of CS and BCVA, was derived and analyzed. RESULTS: The mean (± SD) BCVA was 0.08 ± 0.10 log MAR (approximately 20/25 Snellen equivalent), the mean CS was 1.38 ± 0.17, and the mean HVF MD was −7.22 ± 8.10 dB. CS and HVF MD correlated significantly (r = 0.51, p < 0.001). BCVA correlated significantly with large letter CS (r = −0.22, p = 0.03), but not with HVF MD (r = −0.12, p = 0.26). A subset of the subject sample (approximately 20%) had moderate to no field loss (≤−6 dB MD) and minimal to no BCVA loss (≤0.3 log MAR), but had poor letter CS. AUCSF was correlated significantly with HVF MD (r = 0.46, p < 0.001). CONCLUSIONS: The present study is the first to evaluate letter CS in glaucoma using the digital MSSS-II display. Letter CS correlated significantly with standard HVF MD measurements, suggesting that letter CS may provide a useful adjunct test of visual function for glaucoma patients. Additionally, the significant correlation between HVF MD and the combined index of CS and BCVA (AUCSF) suggests that this measure may also be useful for quantifying visual dysfunction in glaucoma patients.